SUSCEPTIBILITY OF RIFAMPICIN-ISONIAZID RESISTANT MYCOBACTERIUM TUBERCULOSIS ISOLATES AGAINST LEVOFLOXACIN - Kurniawan, Alvin Hartanto; Mertaniasih, Ni Made; Soedarsono, S. (BALI MEDICAL JOURNAL, 2016)
Background: Tuberculosis (TB) is a high burden disease in Indonesia with multidrug-resistant (MDR) TB incidence started to increase. Treatment success of MDR-TB globally was low in number than it was targeted which was especially caused by fluoroquinolone resistance. One of the fluoroquinolone is levofloxacin, an antibiotic that has been widely used irrationally as antimicrobial treatment. Therefore, this study investigated the sensitivity and MBC of MDR Mycobacterium tuberculosis isolates against Levofloxacin. Method: The susceptibility test for MDR -Mycobacterium tuberculosis on levofloxacin by standard method with levofloxacin were on concentrations 0,5 ?g/ml, 1 ?g/ml, and 2 ?g/ml. Sample of 8 strains MDR-Mycobacterium tuberculosis were cultured with each concentrations on Middlebrook 7H9 for 1 week incubation. Next, each of the incubated concentration was subcultured on solid media Middlebrook 7H10 for 3 weeks incubation. Colonized agar plates after 3 weeks incubation were confirmed with acid-fast stain. Results: On MB 7H10 with levofloxacin concentration 2 ?g/ml showed bactericidal effect 100% by no MDR Mycobacterium tuberculosis colony grew (0/8) while the MB 7H10 with levofloxacin concentration 1 ?g/ml and 0,5 ?g/ml showed the bactericidal effect 37,5% and 25% respectively. The colonized agar plate implied that the MDR Mycobacterium tuberculosis with levofloxacin concentration 1 ?g/ml (5/8) and 0,5 ?g/ml (6/8) grew well. Conclusion: Levofloxacin concentration 2 ?g/ml was susceptible on MDR Mycobacterium tuberculosis. The concentration 2 ?g/ml of levofloxacin could be considered as MBC.
Keywords: Tuberculosis; Mycobacterium tuberculosis; Levofloxacin. Susceptibility Test